2017
DOI: 10.1093/mnras/stx384
|View full text |Cite
|
Sign up to set email alerts
|

Observations of V0332+53 during the 2015 outburst using Fermi/GBM, MAXI, Swift and INTEGRAL

Abstract: We present the lightcurves, spectra, and hardness-intensity diagram (HID) of the high mass X-ray binary V0332+53 using Fermi/GBM, MAXI, Swift /BAT, and INTE-GRAL through its 2015 Type II outburst. We observe characteristic features in the X-ray emission (2-50 keV) due to periastron passages, the dynamical timescale of the accretion disc, and changes within the accretion column between a radiationdominated flow and a flow dominated by Coulomb interactions. Based on the HID and the light curves, the critical lum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The most recent giant outburst of the source took place in 2015, followed by a mini-outburst in 2016 (Cusumano et al 2016;Tsygankov et al 2016;Baum et al 2017). In Doroshenko et al (2017); Vybornov et al (2018) it was found that the above-mentioned anticorrelation between CRSF energy and luminosity breaks at low fluxes, suggesting the change in accretion regimes (from super-to sub-critical, see Basko & Sunyaev 1976;Mushtukov et al 2015a).…”
Section: System V 0332+53mentioning
confidence: 96%
See 1 more Smart Citation
“…The most recent giant outburst of the source took place in 2015, followed by a mini-outburst in 2016 (Cusumano et al 2016;Tsygankov et al 2016;Baum et al 2017). In Doroshenko et al (2017); Vybornov et al (2018) it was found that the above-mentioned anticorrelation between CRSF energy and luminosity breaks at low fluxes, suggesting the change in accretion regimes (from super-to sub-critical, see Basko & Sunyaev 1976;Mushtukov et al 2015a).…”
Section: System V 0332+53mentioning
confidence: 96%
“…In our fits, the spectral width of the line was poorly constrained but had a value typically ∼ 0.3 ± 0.1 keV. Therefore we fixed the width at 0.3 keV, a value similar to the results of Caballero-García et al (2016); Baum et al (2017). With applied systematic errors (sect.…”
Section: Light Curve and Long-term Spectral Evolutionmentioning
confidence: 98%